Influence of inoculum on performance of anaerobic reactors for treating municipal solid waste - Lopes, W. S.; Leite, V. D.; Prasad, S. (Elsevier B.V., 2004)
The influence of bovine rumen fluid inoculum during anaerobic treatment of the organic fraction of municipal solid waste (MSW) was studied in this work. The parameters adopted for evaluation were the biostabilization constant of total volatile solids (TVs) and the biostabilization time of the chemical oxygen demand (COD) applied to the reactors. The work was realized in four anaerobic batch reactors of 20 1 capacity each, during a period of 365 days. The proportions between MSW/inoculum loaded in the reactors were Reactor A (100%/0%), Reactor B (95%/5%), Reactor C (90%/10%) and Reactor D (85%/15%). The necessary time for biostabilization of half of the applied COD was 459, 347, 302 and 234 days and the average of methane concentration in the biogas produced was 3.6%, 13.0%, 25.0% and 42.6% for Reactors A, B, C and D, respectively. The data obtained affirm that the inoculum used substantially improved the performance of the process. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: inoculum; biostabilization; municipal solid waste; anaerobic treatment; batch reactors